Being an academic dermatologist in Turkey: Young academic dermatologists' perspectives on dermatology - SALMAN, ANDAÇ (DERI ZUHREVI HASTALIKLAR DERNEGI, 2021)
Background and Design: This study aims to examine the characteristics of young Turkish academic dermatologists and identify the positive and negative aspects of being an academic dermatologist from their perspectives. Materials and Methods: A cross-sectional, electronic questionnaire was mailed to dermatologsts who work as an assistant professor or faculty member of dermatology in a university or training and research hospital in Turkey. The questions were prepared to evaluate views of young academic dermatologsts on academic dermatology. Results: A total of 37 assistant professors and faculty members of dermatology responded to the survey. The top three reasons for pursuing an academic career and the most satisfying and pleasing aspects of academic life were the opportunity to teach, do research, and deal with complex diseases. Compensation was the least frequently (5.4%) chosen reason to pursue an academic life. Insufficient time (70.3%) was stated to be the most challenging aspect of research activities. The most cited issues respondents stated that they needed support or education were data analysis (78.4%) and training abroad (67.6%). Conclusion: To our knowledge, this is the first study to evaluate academic dermatology in Turkey. We believe that the present study results provide insight into academic dermatology and might help increase the awareness of the dermatology residents who pursue an academic career.
Keywords: Academic; dermatology; Turkey